Relationship with Christ and being led by The Holy Spirit are key to Carrying out The mission in The Acts of The Apostles - Jimmy Agustin Siregar (Devotion : Journal of Research and Community Service, 2026)
This study examines the relationship with Christ and the empowerment of the Holy Spirit as the foundation for mission in the Acts of the Apostles. The research is motivated by the tendency of many contemporary churches to rely more on pragmatic strategies than on spiritual formation in carrying out God’s mission. In addition, a research gap exists because relatively few integrative studies have examined the relationship between Christology and Pneumatology within the missionary framework of the early church. This study aims to analyze how a relationship with Christ serves as the spiritual and theological foundation of mission and how the Holy Spirit leads, empowers, and sustains the church in fulfilling God’s mission. The research employs a qualitative method using a library research approach, supported by thematic, narrative, and theological analyses of the Book of Acts. The findings reveal that the success of the early church’s mission did not depend on human ability but on an intimate relationship with Christ and complete dependence on the Holy Spirit. The Holy Spirit functioned as the primary agent of mission by empowering evangelism, sustaining the church, and guiding the spiritual growth of believers. This study concludes that a relationship with Christ and the empowering work of the Holy Spirit are inseparable aspects of the work of the Triune God and constitute the primary foundation for a biblical, Spirit-led, and contextually relevant mission in the contemporary church.